Species‐specific clinical characteristics of human coronavirus infection among otherwise healthy adolescents and adults. Issue 2 (2nd February 2018) - Bouvier, Monique; Chen, Wei‐Ju; Arnold, John C.; Fairchok, Mary P.; Danaher, Patrick J.; Lalani, Tahaniyat; Malone, Leslie; Mor, Deepika; Ridoré, Michelande; Burgess, Timothy H.; Millar, Eugene V.
Abstract : Human coronavirus (HCoV) is a known cause of influenza‐like illness (ILI). In a multisite, observational, longitudinal study of ILI among otherwise healthy adolescents and adults, 12% of subjects were PCR‐positive for HCoV. The distribution of species was as follows: HCoV‐OC43 (34%), HCoV‐229E (28%), HCoV‐NL63 (22%), and HCoV‐HKU1 (16%). We did not observe species‐specific differences in the clinical characteristics of HCoV infection, with the exception of HCoV‐HKU1, for which the severity of gastrointestinal symptoms trended higher on the fourth day of illness.